Export of products of the agricultural industrial complex of Ukraine in the period March 2022–January 2024: analysis of seasonal fluctuations - Totska, Olesia Leontiivna (University of Agronomic Sciences and Veterinary Medicine of Bucharest. Ceres Publishing House., 2024)
The purpose of this article is to analyze seasonal fluctuations in the export of agricultural crops from Ukraine in the period March 2022–January 2024. The research used data from a dashboard created by the Office for Entrepreneurship and Export Development together with the Ministry of Agrarian Policy and Food of Ukraine and the Ministry of Infrastructure of Ukraine. In March-April 2022, the total export of a number of types of agricultural products was very low, but over time began to increase significantly and reached its peak in March 2023. This happened due to the adaptation of Ukrainian producers and exporters of agricultural products to the emergence of new challenges. Among Ukrainian agricultural products, corn and wheat have the greatest export potential (over 1.1 million tons per month on average), sunflower oil, meal, rape, soybeans, barley, and sunflower seeds have less potential (over 150,000 tons per month on average), the smallest potential has soybean oil (more than 20,000 tons per month on average). Most types of agricultural products have two distinct phases of export seasonality: growth and decline. In the analyzed period, a seasonal increase in exports was observed for corn – in November-March; wheat – September-February; meal – August-February; rape – August-December; soybeans – October-February. For other types of products, export growth and decline phases changed more often: the increase in sunflower oil exports occurred in November-February and September; barley – in September-February and July; sunflower seeds – in October-December, February and May-July; soybean oil – in October-January and May-July.

Метою цієї статті є аналіз сезонних коливань експорту агрокультур з України у період березень 2022 р.–січень 2024 р. Для дослідження використано дані дашборду, створеного Офісом з розвитку підприємництва та експорту спільно з Міністерством аграрної політики та продовольства України та Міністерством інфраструктури України. У березні-квітні 2022 р. сукупний експорт низки видів продукції АПК був дуже низьким, але з часом почав суттєво збільшуватися і досягнув свого піку в березні 2023 р. Це відбулося завдяки адаптації українських виробників і експортерів агропродукції до появи нових викликів. Найбільший експортний потенціал серед української аграрної продукції має кукурудза та пшениця (у середньому понад 1,1 млн тонн на місяць), менший – олія соняшникова, шроти, ріпак, соєві боби, ячмінь і насіння соняшника (у середньому понад 150 тис. тонн на місяць), найменший – олія соєва (у середньому понад 20 тис. тонн на місяць). Більшість видів продукції АПК мають яскраво виражені дві фази сезонності експорту: зростання та спаду. В аналізованому періоді сезонне збільшення експорту спостерігалося для кукурудзи – в листопаді-березні; пшениці – вересні-лютому; шротів – серпні-лютому; ріпака – серпні-грудні; соєвих бобів – жовтні-лютому. Для інших видів продукції фази зростання та спаду експорту змінювалися частіше: збільшення експорту олії соняшникової відбувалося в листопаді-лютому та вересні; ячменю – у вересні-лютому й липні; насіння соняшника – у жовтні-грудні, лютому та травні-липні; олії соєвої – у жовтні-січні й травні-липні.
Keywords: export; agricultural crops; Ukraine; seasonal fluctuations; analysis; експорт; аграрні культури; Україна; сезонні коливання; аналіз